Associations between cruciferous vegetable intake and selected biomarkers among women scheduled for breast biopsies. Issue 7 (2nd September 2015) - Zhang, Zhenzhen; Atwell, Lauren L; Farris, Paige E; Ho, Emily; Shannon, Jackilen
Abstract: Objective: To examine the relationship between dietary cruciferous vegetable intake and selected tumour biomarkers for histone acetylation (H3K9ac, H3K18ac, HDAC3 and HDAC6), proliferation (Ki-67) and cell-cycle regulation (p21) from breast tissue. Design: The study used baseline data of women recruited to participate in a clinical trial of sulforaphane supplement. Dietary cruciferous vegetable intake was collected through a validated Arizona Cruciferous Vegetable Intake Questionnaire. Breast tissue was obtained from biopsy samples. Spearman correlations were calculated between intake of specific cruciferous vegetables and biomarkers. Tissue biomarkers were log2 -transformed to obtain approximate normality. Linear regression analyses were conducted to examine associations between cruciferous vegetable intake and biomarkers adjusting for age and use of non-steroidal anti-inflammatory drugs. False discovery rate (FDR) was used to account for multiple comparisons. Setting: Clinical trial baseline. Subjects: Fifty-four women who had abnormal mammogram findings and were scheduled for breast biopsy. Results: Mean intake of total cruciferous vegetables from all food sources was 81·7 (sd 57·3) g/d. Mean urinary total sulforaphane metabolites was 0·08 (sd 0·07) µm /mm creatinine. Total cruciferous vegetable intake was inversely associated with Ki-67 protein expression in breast ductal carcinoma in situ (DCIS) tissue ( β =−0·004;se =0·001; FDR q value=0·03), but not in benign or invasive ductal carcinoma (IDC) tissue. No association was found for other biomarkers measured (HDAC3, HDAC6, H3K9, H3K18 and p21) in all tissues examined (benign, DCIS and IDC). Conclusions: The present study sought to provide additional evidence for the potential role of sulforaphane in histone acetylation and cell proliferation. Here, we report that total cruciferous vegetable intake is associated with decreased cell proliferation in breast DCIS tissue.